Financial, Public and Regional Economics: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
This study examines long run and causal relationship between fiscal decentralization and economic development in Nigeria using annual data from 1970-2011. Both sub-national expenditures ratio and sub national revenue ratio were used to measure fiscal decentralisation in Nigeria. The result of the analysis showed that the federally allocated expenditures to sub-national has been greater than its corresponding allocated revenue in Nigeria and this has became pronounced from the year 1999 up till date under the administration of a dominant political party known as People Democratic Party (PDP) in Nigeria. Using VECM, the study found that fiscal decentralisation is cointegrated with economic development in Nigeria. That is, there is a long run relationship between fiscal decentralisation and economic development. The results from the VEC granger causality test showed a unidirectional causality run from economic development to fiscal decentralization i.e. economic development granger causes fiscal decentralization (only sub-national revenue decentralization ratio) in Nigeria. By implication, economic benefits derived from fiscal decentralization are the products of economic development simply because as economy is developing, these benefits emerge in Nigeria.